The Estimation of Enhanced Outcoupling for OLEDs with Isotropically Scattering Materials - Mongelli, Guy Francis (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2019)
This manuscript uses classical geometrical optics and the convergence of an infinite Fourier series to derive a mathematical equation for the out-coupling efficiency of classical scattering-enhanced OLEDs. Several simple assumptions are made regarding how light interacts with scattering media. It describes the extent of efficiency improvement in terms of nanoparticle properties and the revised out-coupling efficiency limitation. The albedo is the ratio of scattering to extinction cross-sections, where extinction is scattering plus absorption. Albedo indicates how much of the light that interacts with a particle is re-emitted or retained to move around the OLED device further. An estimation of the out-coupling efficiency observed when nanoparticles of various albedo values are incorporated into the simplified OLED structure is performed.